Estresse de dominância e respostas metabólicas da tilápia-do-Nilo - Genovez, Lara Wichr [UNESP] (2014)
The dominance hierarchy and agonistic confrontation cause stress to the animals. This study aimed to quantify the effect of stress after the establishment of social hierarchy evaluating metabolic responses between the juvenile Nile tilapia. 20 male fish were distributed in 10 tanks with a capacity of 110 liters, adopted an outline fully cazualizado total of five treatments with four replications. The animals were fed a practical diet containing 28.0% crude protein and 3000 kcal of digestible energy. The hierarchical division of the individuals were in dominant and submissive second Falter (1983). For the treatment of visual communication, aquaria were divided plates with translucent glass, where the animals had no physical contact not having any type of contact water conspecific eat; for the treatment of chemical communication had a pumping system that homegeneizava water animals, without any eye contact with the conspecific. The isolated animal received no water no other fish and even had eye contact. The effect of the hierarchical stress ratings were measured by means of three studies: a) digestibility, b) and c gastrointestinal transit time) morphology of the intestinal epithelium of the fish. The data gastrointestinal transit time were represented as graphs and morphometric data were evaluated by multivariate analysis of variance, considering the pair villi height (AV) and crypt depth (PC). Based on the results obtained it can be concluded that the hierarchical stress has significant effect on the gastrointestinal transit, increasing the speed of transit of food intake within two hours in submissive animals and the proximal portion of the intestine is the most appropriate to evaluate the effect of hierarchical stress by pair (AV: PC).